Methodology for determining climate change by analysis of impurity concentrations in the glacier - Curmei, M.D.; Makarenko, T.I.; Melnyk, V.I.; Klishevich, G.V. (Український антарктичний журнал, 2019)
The work contains the analysis of possible distributions of aerosol impurities through the glacier depth in those regions of Antarctica, where synoptic maps have shown stabilization of cyclones; and based on this analysis a methodology has been proposed for the determination of climatic parameter changes (average temperature and atmospheric precipitation amount) over a long time period. В роботі проведено аналіз можливих комбінацій розподілу аерозольних домішок вздовж товщі льодовика в тих районах Антарктиди, де на основі синоптичних мап виявлена стабілізація циклонів, і на його основі запропонована методика зміни кліматичних параметрів (середня температура і кількість атмосферних опадів) протягом великого проміжку часу.